Alternative Transcription Factor ς(B) Is Involved in Regulation of Biofilm Expression in a Staphylococcus aureus Mucosal Isolate - Rachid, Shwan (American Society for Microbiology, 2000)
Osmotic stress was found to induce biofilm formation in a Staphylococcus aureus mucosal isolate. Inactivation of a global regulator of the bacterial stress response, the alternative transcription factor ς(B), resulted in a biofilm-negative phenotype and loss of salt-induced biofilm production. Complementation of the mutant strain with an expression plasmid encoding ς(B) completely restored the wild-type phenotype. The combined data suggest a critical role of ς(B) in S. aureus biofilm regulation under environmental stress conditions.